Development and tri-objective optimization of a novel biomass to power and hydrogen plant: A comparison of fueling with biomass gasification or biomass digestion. (1st January 2022) - Cao, Yan; Dhahad, Hayder A.; Hussen, Hasanen M.; Anqi, Ali E.; Farouk, Naeim; Issakhov, Alibek
Abstract: Regarding the low energy density of solid biomass, it usually is converted to gaseous bio-fuels to be utilized in power generation systems. In this regard, the biomass gasification and digestion are of two major conversion routes. The main goal of this research is to make a comparison between biomass gasification and digestion to fuel a power and hydrogen cogeneration plant. The proposed plant is composed of a micro-scale gas turbine and an absorption power cycle for exhaust waste heat recovery of the gas turbine. The generated power by the absorption cycle is utilized in an alkaline electrolyzer for hydrogen production. Thermodynamic, economic and electrochemical models are developed to simulate and investigate the systems performances from exergy, economic and environmental standpoints. Also to determine the best operating conditions, tri-objective optimization is conducted based on maximizing the exergy efficiency and minimizing CO2 emission and product cost. The results indicate that the digester-based system yields higher values of power and hydrogen production, and exergy efficiency as well as lower value of CO2 emission compared to gasifier-based system. It implies that selection of the better system between the two considered ones depends on the user/designer special criteria. Highlights: Proposal of an innovative biomass fueled cogeneration of power and hydrogen plant. Comparison between biomass gasification and digestion to fuel the proposed system. Tri-objective optimization based on cost, emission and efficiency. Better performance for digester-based system from emission and efficiency viewpoints. Better performance for gasifier-based system from economic viewpoint.